Characterization of sky conditions over Ile-Ife, Nigeria, based on 19921998 solar radiation observations - Emmanuel Chilekwu Okogbue; Joseph Adesola Adedokun (Meteorologische Zeitschrift, 2002)
Daily global and diffuse irradiance data monitored on a horizontal surface at Ile-Ife (7.5°N, 4.5°E), Nigeria, during the period 1992-1998, have been used to calculate values of the clearness index KT, and diffuse ratio K'd and the diffuse coefficient Kd for the station. A characterisation of the sky conditions over the station, based on the calculated KT values for the 7 years of data is presented. The annual sky conditions at the station have been shown to exhibit five characteristic patterns comprising of one distinct dry season and four distinct wet (rainy) seasons. Statistical monthly KT curves have also been established for Ile-Ife after LIU and JORDAN (1960). The possibility of using these monthly KT curves to establish approximate statistical distribution of the daily global radiation for other cities within similar latitude and longitude underscores their importance.